The Effect of Hydrothermal Aging on the Non-Isothermal Crystallization Behavior of Polyamide 6 - Zhang, Xinyang (International Journal of Materials Science and Technology Studies, 2025)
Polyamide 6 (PA6) is an important semi-crystalline engineering plastic widely used in electrical appliances, automotive materials, and other applications. However, PA6 is highly susceptible to moisture absorption, which can significantly alter its physicochemical properties. In this study, PA6 was synthesized via anionic ring-opening polymerization, and immersion tests were conducted in accordance with ISO 175:2010. The influence of environmental factors on the non-isothermal crystallization behavior of PA6 was investigated. The Mo equation was successfully employed to characterize the entire non-isothermal crystallization process. The obtained kinetic parameters provide valuable insights for predicting the performance of PA6 under practical conditions and serve as a reference for the modification and optimization of PA6.